A comparative study between SPWM and SHE-PWM modulation techniques for DC-AC inverters - Aboadla, Ezzidin Hassan; Tohtayong, Majdee; Aznan, Khairil Azhar; Khalil, Ashraf; Khan, Sheroz; Habaebi, Mohamed Hadi; Gunawan, Teddy Surya; Hamida, Belal Ahmed; Yaacob, Mashkuri (2017)
DC-AC Inverters are basically used to convert renewable sources DC, like solar energy or storage batteries into AC power. However, the outputs of these converters contain undesirable harmonic distortion due to the ON and OFF switching. There are a number of modulation schemes employed to control ON-OFF the switching of IGBT (or MOSFET) of Inverters and to mitigate these harmonics effectively. The most popular modulation methods in this regard are Sinusoidal Puls Width Modulation (SPWM) and Selective Harmonics Elimination Puls Width Modulation (SHE-PWM). The common parameters between two techniques are modulation index and the number of pulses. A minimum Total Harmonic Distortion (THD) is used as a criterion to comparing results by both techniques. This paper demonstrates the comparison between SPWM and SHEPWM implemented in the unipolar inverter. To assess and validate the utility of the techniques, simulation results are obtained using MATLAB software.